Empowerment of Community Creative Economy Through the Islamic Education Assembly (Majelis Taklim) - Susanti , Handayani Indah (Universitas Pembangunan Nasional Veteran Jakarta, 2024)
The activities of the Islamic Education Assembly require intervention in the form of empowerment through the strengthening of productive socio-economic capacities. In addition to focusing on its main activities in Islamic studies, the Islamic Education Assembly also organizes creative economic activities conducted by its members. However, these activities face challenges such as limited connections with external communities, dependency on others, and inadequate facilities and infrastructure that affect the effectiveness of community-based economic empowerment. This study aims to uncover the patterns and strategies of community economic empowerment used by the Islamic Education Assembly administrators and facilitators, as well as to identify the supporting and inhibiting factors in the empowerment process. The research adopts a qualitative approach, utilizing fieldwork through interviews, observations, and document analysis. The findings reveal that the empowerment process is carried out through a bottom-up approach based on the community's own initiatives. The Mezzo-Level Strategy was effectively implemented, focusing on empowering groups through education and training. Supporting factors include (a) high community participation, (b) loyalty of the congregation and community, (c) demands from congregants and members for training, (d) strategic location, and (e) flexible timing. Conversely, the key inhibiting factors are (a) limited connections with external communities, (b) dependency on others, and (c) inadequate facilities and infrastructure. These findings suggest that fostering community participation, strengthening institutional systems, and reducing dependency are critical for achieving sustainable community empowerment. The study highlights the potential of the Islamic Education Assembly to drive socio-economic development through creative economic activities tailored to local needs, provided the challenges are addressed strategically. Kegiatan Majelis Taklim membutuhkan intervensi dalam bentuk pemberdayaan melalui penguatan kapasitas sosial ekonomi produktif. Selain fokus pada kegiatan utama dalam kajian keislaman, Majelis Taklim juga mengadakan kegiatan ekonomi kreatif yang dilakukan oleh para anggotanya. Namun, kegiatan ini menghadapi tantangan berupa kurangnya koneksi dengan komunitas luar, ketergantungan terhadap pihak lain, dan keterbatasan fasilitas serta prasarana yang memengaruhi efektivitas pemberdayaan ekonomi berbasis komunitas. Penelitian ini bertujuan untuk mengungkap pola dan strategi pemberdayaan ekonomi masyarakat yang digunakan oleh pengurus Majelis Taklim dan pemberdaya serta menemukan faktor pendukung dan penghambat dalam proses pemberdayaan tersebut. Metode penelitian menggunakan pendekatan kualitatif dengan penelitian lapangan melalui wawancara, observasi, dan analisis dokumen. Hasil penelitian menunjukkan bahwa proses pemberdayaan dilakukan dengan pendekatan bottom-up yang didasarkan pada inisiatif masyarakat sendiri. Strategi pemberdayaan yang diterapkan menggunakan Strategi Aras Mezzo, yang berfokus pada pemberdayaan kelompok melalui pendidikan dan pelatihan. Faktor pendukung meliputi (a) tingginya partisipasi masyarakat, (b) loyalitas jamaah dan komunitas, (c) permintaan pelatihan dari jamaah dan anggota, (d) lokasi strategis, dan (e) waktu yang fleksibel. Sebaliknya, faktor penghambat utama adalah (a) keterbatasan koneksi dengan komunitas eksternal, (b) ketergantungan pada pihak lain, dan (c) fasilitas serta infrastruktur yang tidak memadai. Hasil Temuan dari penelitian ini menunjukkan bahwa meningkatkan partisipasi masyarakat, memperkuat sistem kelembagaan, dan mengurangi ketergantungan merupakan langkah penting untuk mencapai pemberdayaan masyarakat yang berkelanjutan. Penelitian ini menyoroti potensi Majelis Taklim dalam mendorong pengembangan sosial-ekonomi melalui kegiatan ekonomi kreatif yang disesuaikan dengan kebutuhan lokal, asalkan tantangan-tantangan tersebut dapat diatasi secara strategis.